A novel mechanism of 6-methoxydihydroavicine in suppressing ovarian carcinoma by disrupting mitochondrial homeostasis and triggering ROS/ MAPK mediated apoptosis - Zhang, Huachang; Shangguan, Fugen; Zhang, Lan; Ma, Nengfang; Song, Shuling; Ma, Li; Liu, Chuntong; Liu, Mengke; An, Jing; Li, Hua; Cao, Qizhi (Frontiers in Pharmacology, 2023)
Alkaloids derived from M. cordata (Papaveraceae family), have been found to display antineoplastic activity in several types of cancer. However, the antitumor effects and mechanisms of a new alkaloid extracted from the fruits of M. cordata fruits, named 6-Methoxydihydroavicine (6-ME), remains unclear in the case of ovarian cancer (OC). Here, we reported for the first time that 6-ME exhibits OC cells growth in vitro and in vivo. Meanwhile, we found that 6-ME showed great antineoplastic activities by disrupting mitochondria homeostasis and promoting apoptosis in OC cells. Further investigation of the upstream signaling of apoptosis revealed that 6-ME-triggered apoptosis was induced by reactive oxygen species (ROS)-mediated MAPK activation and mitochondria dysfunction in OC cells. Disturbance of oxaloacetic acid (OAA) metabolism, a crucial metabolite that has been shown abled to counteract the cytotoxicity by 6-ME in this study, leads to deficiency of OAA, thereby causing accumulation of ROS levels by eliminating NADPH content. In summary, our data show that 6-ME exhibits cytotoxicity to OC cells in a ROS-dependent manner by interrupting mitochondrial respiration homeostasis and inducing MAPK-mediated apoptosis. This evidence suggests that 6-ME is a promising remedy for OC intervention.